1972
DOI: 10.1136/gut.13.3.176
|View full text |Cite
|
Sign up to set email alerts
|

Gastric emptying of solid meals after truncal vagotomy and pyloroplasty in human subjects

Abstract: SUMMARY Gastric emptying of isotopically labelled solid meals was studied in normal human subjects and in patients at different intervals after truncal vagotomy and Heineke-Mikulicz pyloroplasty.One to four weeks after vagotomy and pyloroplasty gastric emptying was delayed grossly in some patients regardless of the completeness of vagotomy. Patients with gross delay had symptoms of gastric retention. Eight weeks later emptying had returned towards normal and one or more years after vagotomy and pyloroplasty em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
0
1

Year Published

1974
1974
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(29 citation statements)
references
References 9 publications
4
24
0
1
Order By: Relevance
“…Pumping action of the antrum is weakened after vagal denervation (Cowley et al 1971;Medina 1982), and animals subjected to a total vagotomy show gastric distension and retention (Kraly et al 1986). In the present study, a greater amount of gastric content and greater gastric distension were observed in the vagotomized exercise group than in the vagotomized sedentary group after 24-h fasting.…”
Section: Fig 3 Antral and Duodenal Motilities In The Vagotomized Ramentioning
confidence: 99%
“…Pumping action of the antrum is weakened after vagal denervation (Cowley et al 1971;Medina 1982), and animals subjected to a total vagotomy show gastric distension and retention (Kraly et al 1986). In the present study, a greater amount of gastric content and greater gastric distension were observed in the vagotomized exercise group than in the vagotomized sedentary group after 24-h fasting.…”
Section: Fig 3 Antral and Duodenal Motilities In The Vagotomized Ramentioning
confidence: 99%
“…However, the rate at which emptying returns to normal may be related to gastric outlet size, as the emptying times of the patients with a large outlet had returned to normal limits 4-6 months postoperatively, whereas that of those with a relatively small outlet was still delayed. However, previous studies (Cowley et al, 1972) have shown that the gastric emptying of patients with smaller gastric outlets also returns to normal more than 1 year after operation.…”
Section: Discussionmentioning
confidence: 89%
“…Cowley et al (1972) found that gastric emptying of solid meals was slower than that of a normal control group, both at 1 4 weeks and later at 1 4 months after vagotomy and pyloroplasty. However, emptying had returned to normal in patients tested more than 1 year after operation.…”
mentioning
confidence: 84%
“…On peut s'attendre ~t un retour ~t la normale dans les trois ans. 13 Le reflux gastro-oesophagien est associ6 ~ une rttention significative de la nourriture solide dans 57% des patients alors que les autres ont une vidange normale ou acctltrte. Le reflux gastro-oesophagien et Pulc~re gastrique ne retardent pas la vidange des liquides.…”
Section: La Physiologic Gastriqueunclassified